1998
DOI: 10.1002/(sici)1097-0290(19980420)58:2/3<258::aid-bit20>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite-balancing techniques vs.13C tracer experiments to determine metabolic fluxes in hybridoma cells

Abstract: The estimation of intracellular fluxes of mammalian cells using only mass balances of the relevant metabolites is not possible because the set of linear equations defined by these mass balances is underdetermined. In order to quantify fluxes in cyclic pathways the mass balance equations can be complemented with several constraints: (1) the mass balances of co‐metabolites, such as ATP or NAD(P)H, (2) linear objective functions, (3) flux data obtained by isotopic‐tracer experiments. Here, these three methods are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…However, if the pseudo steady state assumption during a phase is justified, it can give a useful overview of its average metabolism [55]. The information obtained by flux balance analysis can be validated [56] or further enriched by specific labelling information [57] to resolve reversible, cyclic or parallel fluxes as for example pentose phosphate pathway split [58, 59]. …”
Section: Discussionmentioning
confidence: 99%
“…However, if the pseudo steady state assumption during a phase is justified, it can give a useful overview of its average metabolism [55]. The information obtained by flux balance analysis can be validated [56] or further enriched by specific labelling information [57] to resolve reversible, cyclic or parallel fluxes as for example pentose phosphate pathway split [58, 59]. …”
Section: Discussionmentioning
confidence: 99%
“…The network includes 8 extracellular substrates (glucose, arginine, asparagine, cysteine, glutamine, isoleucine, leucine, and serine), 6 metabolic products (biomass, lactate, alanine, glutamate, glycine, and lipids) and 35 balanced intracellular metabolites. Constraints from cofactor metabolites such as ATP and NAD(P)H were excluded because these balances have been shown to produce unreliable results in mammalian systems (Bonarius et al, 1998). Refer to Supplementary Materials for a detailed description of the model formulation and assumptions.…”
Section: Methodsmentioning
confidence: 99%
“…While initially mostly applied to microorganisms, 13 C-metabolic flux analysis have now been conducted on many relevant animal cell lines, including hybridoma cells [27][28][29], CHO cells [30], A549 lung carcinoma cells [31], hepatic cells [32] and brown adipocytes [33]. One key point emerging from some of these studies are the significant discrepancies observed between fluxes determined from labeling and the ones calculated from metabolite balancing [32,34], highlighting the need for additional independent constraints in comprehensive metabolic studies.…”
mentioning
confidence: 99%